Neuroparasitology and tropical neurology - García, Héctor H.; Tanowitz, Herbert B.; Del Brutto, Oscar H. (Handbook of clinical neurology, 2013)
Neurological aspects of neglected tropical diseases: an unrecognized burden -- Pathophysiology and characteristics of parasitic infections -- Mechanisms of CNS invasion and damage by parasites -- Immunodiagnosis of CNS parasitic infections -- Imaging of parasitic infections of the central nervous system -- Pathology of CNS parasitic infections -- Protozoa -- Cerebral malaria -- American trypanosomiasis -- Toxoplasmosis -- Entamoeba histolytica brain abscess -- Infections with free-living amebae -- Human African trypanosomiasis -- Microsporidiasis -- Neurological manifestations of human leishmaniasis -- Neurological manifestations of human babesiosis -- Nematoda -- Eosinophilic meningitis -- Toxocariasis -- Strongyloides stercoralis infection complicating the central nervous system -- Neurological manifestations of filarial infections -- Neurotrichinellosis -- Baylisascaris larva migrans -- Other helminthic infections: Ascariasis, Dracontiasis, Lagochilascariasis, Micronemiasis -- Trematoda -- Schistosomiasis of the nervous system -- Paragonimiasis -- Direct and indirect affection of the central nervous system by Fasciola infection -- Cestoda -- Neurocysticercosis -- Cystic and alveolar echinococcosis -- Other cestodes: sparganosis, coenurosis and Taenia crassiceps cysticercosis -- Other tropical neurological disorders -- Neurological effects of venomous bites and stings: snakes, spiders, and scorpions -- Effects of geohelminth infections on neurological development -- Nutritional disorders in tropical neurology